Covalent modified reduced graphene oxide: Facile fabrication and high rate supercapacitor performances. (10th February 2021) - Wang, Qing; Gao, Haiyan; Zhao, Chenzhuo; Yue, HuiXin; Gao, Guowei; Yu, Jianguo; Kwon, Young-Uk; Zhao, Yongnan
Abstract: Covalent modified graphene (denoted as DMFrGO180) was facilely fabricated by one-step solvothermal process with graphene oxide (GO) and N, N-dimethylformamide (DMF) as the raw materials. DMF serves as not only the solvent but also reactants to generate a reductive amination environment. Solvothermal treatment at 180 °C promotes the reductive amination and produces DMFrGO180 with covalent bonded dimethylamine groups, spit-ball like morphologies, and hierarchical micro- and mesoporous structure. The abundant covalent acidamide bonds render DMFrGO180 plenty of seamless ohmic contact to provide more electron transfer paths. The excellent electrical conductivity enhances and accelerates the redox reversibility of oxygen-containing functional groups to provide more pseudocapacitance. The hierarchical porous structure also accelerates the electrolyte transportation. These features bestow DMFrGO180 excellent rate capability. In three-electrode tests, DMFrGO180 exhibits high gravimetric specific capacitance of 287 F g − 1 at 1 A g − 1 and 192 F g − 1 at 100 A g − 1 . Quasi-solid-state symmetrical two-electrode supercapacitors by using PVA/KOH gel as electrolyte also shows excellent supercapacitive properties with 193.5 F g − 1 and 86.9 F g − 1 at 1 A g − 1 and 50 A g − 1 . Especially, it achieves high energy density 11.35 W h kg −1 at a power density of 649.7 W kg −1 and 5.09 W h kg −1 at power density of 32.4 KW kg −1 . The present results may open a door of graphene oxide for applications in energy storage and conversion fields via a green and energy-efficient process. Graphical abstract: Image, graphical abstract